Granulocyte-macrophage colony-stimulating factor alone or with dacarbazine in metastatic melanoma: a randomized phase II trial - Ravaud, A (Nature Publishing Group, 2001)
The potential antitumoural effect of granulocyte-macrophage colony-stimulating factor (GM-CSF) led us to evaluate GM-CSF alone or with dacarbazine (DTIC) in metastatic melanoma in first line randomized phase II. Treatment was arm A: GM-CSF: 5 μg kg(−1), bid, 14 consecutive days every 21 days and arm B: GM-CSF: 5 μg kg(−1), bid, day 2 to day 19 every 21 days and DTIC: 800 mg m(−2), day 1 of each cycle. 32 patients (pts) were included, 15 pts in arm A and 17 in arm B. All pts had visceral metastatic sites. 9 had only one metastatic site. The median number of cycles given was 2 in arm A and 3 in arm B. 100% and 89.4% of the planned dose of GM-CSF was given in arm A and arm B respectively. No objective response was obtained. 19 pts experienced at least WHO grade 3 toxicity. All pts had fever, 29 had a decrease in performance status and 23 had pain. Grade 3 toxicity were fever (38.7%), decrease in performance status (32.3%), pain (19.4%) and dyspnoea (12.5%). In this study, GM-CSF alone or in association with DTIC did not induce any antitumoural activity with subsequent toxicity. © 2001 Cancer Research Campaign   http://www.bjcancer.com